Detection of Leishmania spp. in Small Non-Flying Mammals (Didelphimorphia and Rodentia) from Bahia, Northeast Brazil - Graziela Baroni de Souza; Hllytchaikra Ferraz Fehlberg; Beatris Felipe Rosa; Cássia Matos Ribeiro; Anaiá da Paixão Sevá; Bianca Mendes Maciel; Martin Roberto Del Valle Alvarez; George Rêgo Albuquerque; Fabiana Lessa Silva (Animals)
This study aimed to identify Leishmania species in small non-flying mammals captured in semi-deciduous forest fragments of the Atlantic Forest and pastures in the Southwest region of Bahia state, Northeast Brazil. A total of 445 animals belonging to 11 different species were captured, the majority being rodents (75.7%; 337), followed by marsupials (24.2%; 108), and the most prevalent species were Cerradomys vivoi, Calomys expulsus, Necromys Lasiurus, and Marmosops incanus. Liver, spleen, kidney, heart, and lung fragments were collected for subsequent molecular diagnosis. Leishmania spp. kDNA amplification in positive samples was performed using real-time polymerase chain reaction (qPCR). Species identification of Leishmania was conducted through nested PCR, followed by sequencing. Leishmania spp. infection was detected in 2.92% (13/445) of the animals. Sequencing revealed that L. infantum infected three animals, while the species of the agent in the other animals could not be determined. The results indicate the presence of Leishmania spp. in the studied region, primarily affecting the local wildlife. These findings not only highlight the risk of transmission to domestic animals and humans in close contact with forest remnants, but also underscore the critical role of these fragments in supporting native fauna. However, it is worth noting that the continuous deforestation of these forest remnants could lead to increased contact between wildlife, domestic animals, and humans, thereby elevating the risk of transmission.